2018
DOI: 10.1007/s10943-018-0609-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Attitudes Toward Death Between University Students Who Receive Nursing Education and Who Receive Religious Education

Abstract: This study aims to compare attitudes toward death between university students who receive nursing education and who receive religious education. This study is cross-sectional in nature. It was conducted with the participation of 197 university students in a university located in the Eastern part of Turkey between June and August, 2017. Data were collected using the socio-demographic form and Turkish form of Death Attitudes Profile-Revised. Of all the students participating in the study, 52.8% received nursing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 16 publications
1
21
0
1
Order By: Relevance
“…For health providers, providing health care to the dying patients and his or her relatives is one of the most painful and stressful responsibilities (Bakan & Arli, 2018). Nurses need to know physical and psychological needs of the patients, to develop a positive attitude toward death, and to accept death to provide better health care.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For health providers, providing health care to the dying patients and his or her relatives is one of the most painful and stressful responsibilities (Bakan & Arli, 2018). Nurses need to know physical and psychological needs of the patients, to develop a positive attitude toward death, and to accept death to provide better health care.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses who find encounters with death and dying very difficult may undergo feelings of insufficiency, helplessness, defensiveness, or distress; and coping mechanisms, such as prevention, being distant, and avoidance may be adopted (Anderson, Kent, & Owens, 2015). Given that dealing with the problems becomes more challenging, and the qualified and holistic care is affected negatively, the health-care providers may have negative feelings, such as grief, depression, despair, fear and anxiety, guiltiness, and have negative attitudes toward death (Bakan & Arli, 2018; Ceyhan, Özen, Zincir, Şimşek, & Başaran, 2018). Ceyhan et al.’s (2018) study showed the most common emotions the nurses had while delivering health care to terminally ill patients were sadness (81.3%) and despair (38.2%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations